Killing commendatore : a novel - Murakami, Haruki, 1949-; Gabriel, Philip, 1953-; Goossen, Ted (New York, NY : Knopf, 2018)
"The much-anticipated new novel from the internationally acclaimed, best-selling author of 1Q84 and Colorless Tsukuru Tazaki and His Years of Pilgrimage, Killing Commendatore is an epic tour de force of love and loneliness, war and art--as well as a loving homage to The Great Gatsby--and a stunning work of imagination from one of our greatest writers"--
"Originally published in Japan as KISHIDANCHO-GOROSHI DAI-ICHI-BU ARAWARERU IDEA HEN and KISHIDANCHO-GOROSHI DAI-NI-BU UTSUROU METAFUA HEN by SHINCHOSHA Publishing Co., Ltd., Tokyo in 2017" -- Verso title page.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School, BRAC University
A single volume version of two books translated from the Japanese.
Keywords: Portrait painters -- Fiction; Painting, Japanese -- Fiction; FICTION / Literary; Psychological fiction; Fantasy fiction; Fiction